Examination of the Relationship of Dairy Product Consumption and Dietary Calcium with Body Mass Index Percentile in Children - Gunther, Carolyn W; Branscum, Paul; Kennel, Julie; Klein, Elizabeth G; Monnat, Laura E; Kaye, Gail (International Journal of Child Health and Nutrition, 2013)
Aim: The purpose of this study was to assess the relationships of dairy product and calcium intake with BMI percentile in children. Methods: In this cross-sectional analysis, the relationships of dairy product (cup equivalents/day) and dietary calcium (mg/day) (measured by 24 hour recall) consumption with BMI percentile [derived from Centers for Disease Control and Prevention (CDC) sex-specific BMI-for-age growth charts] were assessed in 101 healthy U.S. children (ages 8-13). Results: Subject characteristics included (mean + SD): dairy product consumption (2.8 + 1.4 cup equivalents/day), dietary calcium (1039.4 + 431.4 mg/day), and BMI percentile (70.1 + 29.7). Dairy product intake and dietary calcium were inversely related to BMI percentile (p= 0.005). In subjects <85th BMI percentile (n= 50 normal weight and n= 3 underweight), there was an inverse association of dairy product intake with BMI percentile (p= 0.001) and calcium intake with BMI percentile (p< 0.001). However, no association of dairy product consumption or calcium intake with BMI percentile was observed in overweight (85th percentile ≤ BMI < 95th percentile, n= 19) or obese subjects (BMI > 95th percentile, n= 29). Removal of underweight subjects from the analysis only minimally impacted the results. Differences in dietary intake (MyPyramid food groups, calories, macronutrients, micronutrients) among normal, overweight, and obese subgroups were examined. No significant differences were detected between groups, and removing underweight subjects did not change the findings. Conclusions: These results provide the basis for further investigation into a potential role of dairy and calcium in achieving a healthy body weight in children.